Kalanchoe ×robertsonii [K. longiflora × K. rotundifolia] (Crassulaceae subfam. Kalanchooideae), a new, small-growing nothospecies from South Africa - Smith, Gideon F. (Phytotaxa, 2022)
A new nothospecies, Kalanchoe ×robertsonii (Crassulaceae subfam. Kalanchooideae) is described from South Africa. The parents of the nothospecies are K. longiflora and K. rotundifolia, both of which are included in K. subg. Kalanchoe. At maturity, K. ×robertsonii has narrowly oblong to obovate leaves that are in outline closer to those of K. rotundifolia, and small but dense-flowered inflorescences that also more closely resemble those of K. rotundifolia. Overall, plants of K. ×robertsonii, including its leaves, are glaucous to very light green, a colour scheme shared with both its parents. However, especially under conditions of environmental stress, for example high solar irradiation loads, a limited water supply, and low temperatures, the leaves of K. ×robertsonii take on an orange hue, mainly towards the margin, as found in K. longiflora. The flowers of K. ×robertsonii have a more robust corolla tube than in the case of K. rotundifolia, but less so when compared to K. longiflora. The ovate to very slightly elliptic corolla lobes of K. ×robertsonii are bicoloured—bright light orange distally, strongly yellow-infused proximally—and larger than those of K. rotundifolia. Kalanchoe ×robertsonii has considerable architectural appeal, for example as a groundcover, and is hardy in mild-climate regions with limited and unpredictable rainfall.